2D Sandwiched Nano Heterostructures Endow MoSe2/TiO2−x/Graphene with High Rate and Durability for Sodium Ion Capacitor and Its Solid Electrolyte Interphase Dependent Sodiation/Desodiation Mechanism. Issue 48 (5th November 2020) - Liu, Cai; Zhang, Miaoxin; Zhang, Xin; Wan, Biao; Li, Xiaona; Gou, Huiyang; Wang, Yexin; Yin, Fuxing; Wang, Gongkai
Abstract: Nano heterostructures relying on their versatile construction and the breadth of combined functionality have shown great potential in energy storage fields. Herein, 2D sandwiched MoSe2 /TiO2− x /graphene nano heterostructures are designed by integrating structural and functional effects of each component, aiming to address the rate capability and cyclic stability of MoSe2 for sodium ion capacitors (SICs). These 2D nano heterostructures based on graphene platform can facilitate the interfacial electron transport, giving rise to fast reaction kinetics. Meanwhile, the 2D open structure induces a large extent of surface capacitive contribution, eventually leading to a high rate capability (415.2 mAh g −1 @ 5 A g −1 ). An ultrathin oxygen deficient TiO2− x layer sandwiched in these nano heterostructures provides a strong chemical‐anchoring regarding the products generated during the sodiation/desodiation process, securing the entire cyclic stability. The associated sodiation/desodiation mechanism is revealed by operando and ex situ characterizations, which exhibits a strong solid electrolyte interphase (SEI) dependence. The simulations verify the dependent sodiation products and enhanced heterostructural chemical‐anchoring. Assembled SICs based on these nano heterostructures anode exhibit high initial Coulombic efficiency, energy/power densities, and long cycle life, shedding new light on the design of nano heterostructure electrodes for high performance energy storage application. Abstract : Nano heterostructures relying on their versatile construction and the breadth of combined functionality present great potential in energy storage fields. Herein, 2D sandwiched MoSe2 /TiO2− x /graphene nano heterostructures are designed by integrating structural and functional effects of each component, shedding new light on the design of nano heterostructures electrodes for high performance sodium ion capacitors (SICs).